Evolution of a Bidirectional Pediatric Critical Care Educational Partnership in a Resource-Limited Setting - Gardner Yelton, Sarah E.; McCaw, Julia M.; Reuland, Carolyn J.; Steppan, Diana A.; Evangelista, Paula Pilar G.; Shilkofski, Nicole A. (Frontiers in Pediatrics, 2021)
Introduction: Children in resource-limited settings are disproportionately affected by common childhood illnesses, resulting in high rates of mortality. A major barrier to improving child health in such regions is limited pediatric-specific training, particularly in the care of children with critical illness. While global health rotations for trainees from North America and Europe have become commonplace, residency and fellowship programs struggle to ensure that these rotations are mutually beneficial and do not place an undue burden on host countries. We created a bidirectional, multimodal educational program between trainees in Manila, Philippines, and Baltimore, Maryland, United States, to improve the longitudinal educational experience for all participants. Program Components: Based on stakeholder input and a needs assessment, we established a global health training program in which pediatricians from the Philippines traveled to the United States for observerships, and pediatric residents from a tertiary care center in Baltimore traveled to Manila. Additionally, we created and implemented a contextualized simulation-based shock curriculum for pediatric trainees in Manila that can be disseminated locally. This bidirectional program was adapted to include telemedicine and regularly scheduled “virtual rounds” and educational case conferences during the COVID-19 pandemic. Providers from the two institutions have collaborated on educational and clinical research projects, offering opportunities for resource sharing, bidirectional professional development, and institutional improvements. Conclusion: Although creating a mutually beneficial global health partnership requires careful planning and investment over time, establishment of a successful bidirectional educational and professional development program in a limited-resource setting is feasible and benefits learners in both countries.